NILAI-NILAI PIIL PESENGGIRI SEBAGAI CERMINAN KEARIFAN LOKAL DALAM LEGENDA SUMUR PUTRI - Nindi Sintia; Raisya Thania Mawardi; Rahmat Prayogi (STKIP Pesisir Selatan, 2025)
Culture is a complex fact, possessing specific characteristics to some extent, yet also possessing universal qualities. Through the creativity and imagination of writers, culture is then transformed into literary works of great value and depth. This study aims to identify and analyze the values of Piil Pesenggiri reflected in Legenda Sumur Putri by Yuliadi M.R., and explain its relevance as a form of local wisdom of the Lampung people. This study also attempts to show how the legend can be utilized in learning the Lampung language and culture. The method used is descriptive qualitative with a content analysis approach, which focuses on the meaning of cultural values in literary texts. The results of the analysis show that Legenda Sumur Putri contains the main values of Piil Pesenggiri, namely Juluk-Adok (maintaining dignity and self-respect), Nemui-Nyimah (hospitality and openness towards guests), Nengah-Nyappur (mingling harmoniously), Sakai-Sambaian (mutual cooperation and solidarity), and additional values in the form of sincerity and determination. These values reflect the identity, social ethics, and spirituality of the Lampung people. This study confirms that folk legends can function as a means of cultural preservation, character formation, and contextual open material in Lampung language learning.